2019
DOI: 10.1002/pchj.270
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the passage of time and self‐consciousness: What do meditators report?

Abstract: What do humans mean when they say that time passes quickly or slowly? In this article, we try to respond to this question on the basis of our studies on the judgment of the passage of time and its links with the judgment of physical durations. The awareness of the passage of time when consciousness is altered by meditation is also discussed. A dissociation is then made among the "self-time perspective," the "self-duration" (internal duration), and the "world-duration" (external duration). A link is also establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 80 publications
5
48
0
Order By: Relevance
“…However, they "die" of boredom and sadness and time slows down, drags on. The sense of the passage of time is, ultimately, a phenomenological time that is closely related to the self and the sense of existence [13]. As stated by Jean-Paul Sartre, human beings are defined by their acts and their effects on others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they "die" of boredom and sadness and time slows down, drags on. The sense of the passage of time is, ultimately, a phenomenological time that is closely related to the self and the sense of existence [13]. As stated by Jean-Paul Sartre, human beings are defined by their acts and their effects on others.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the challenge of objectively examining just what makes up the experience of each individual, and therefore the role of higher-level cognitive mechanisms (e.g., consciousness, memory, self-awareness) [9][10][11]. Indeed, the judgment of the passage of time can be seen as a mirror of the subjective experience of one's internal state [12][13][14]. For example, contrary to the generally held belief that time seems to pass faster as we get older, some studies have demonstrated that the feeling of the passage of time in the immediate moment is not directly related to age (young adult vs. older adult), but to people's subjective emotional experience and lived activities [10,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Transitory meditative-state effects can similarly be described as an increased sense of presence at the expense of momentary rumination in the past and future. Transitory effects in more experienced meditators have also been described as losing of the sense of self and time, effects which are achieved through an increased presence orientation [11,12,15,43]. Our ‘learning’ effect visible as differences between t2 and t1 corresponds with this concept, as an increased present state at the expense of the past and future awareness accompanies a decrease in the awareness of the self.…”
Section: Discussionmentioning
confidence: 97%
“…A substantial amount of research has also investigated the long-term effects of MMTs and MBIs on basic psychological functions and processes, such as executive functions [8], attention regulation, cognitive flexibility [9], bistable imagery [10], and time perception [11,12,13,14,15,16]. An interesting research branch has begun focusing on the short-term effects of meditation MMTs and MBISs and underlying trait characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Then, they turn to review the literature on hypnosis in relation to the cold control theory of hypnosis, and put mindfulness meditators on the opposite end to highly hypnotizable participants on a continuum of awareness to intention. This difference in metacognition of intentions in these groups is revealed by chronometric measures of the awareness of voluntary action. Droit‐Volet and Dambrun () provide a qualitative study with very experienced meditators. The basic question the authors asked was: what do the extreme sensations of meditators mean, say, when they judge a long meditation session to have passed without a sense of time and self?…”
mentioning
confidence: 99%